Sistema De Información Web Para Mejorar La Gestión Hotelera En La Empresa Korianka E.I.R.L De Trujillo - Montoya Rodríguez, Roxana Katherin (2017)
Today, information systems have become one of the most important resources for organizations. Its use allows continuous modernization of strategies, operations and levels of service, to face the high competitiveness of the market, the improvement of productivity and the increase of the satisfaction of the customers. For this reason, the study objective is to apply the technology through the design and implementation of a Web Information System to improve Hotel Management in the Company KORIANKA E.I.R.L., in Trujillo City. The general design of the research is Cuasi Experimental type (Pre - Test and Post - Test), that is mean; it will manipulate at least the independent variable to see its effect on the dependent variable. Moreover, for the implementation of the Web Information System, the RUP software development methodology will be applied. With the implementation of the Information System will be achieved, mainly, drastically reduce the times used in the Hotel Management processes, in addition the organization will achieve other benefits such as: reduce costs, improve agility and availability of information and significantly increase levels of Satisfaction of the end user, respect to the current process.